Strategi perbankan dalam meningkatkan minat pembelian surat berharga negara oleh masyrarakat untuk mengurangi inflasi - Irawati, Indriana (Maliki Interdisciplinary Journal, 2025)
Indonesia is facing serious economic challenges due to the high inflation rate. The sale of Government Securities (SBN) by the banking sector can help reduce liquidity and maintain the country’s financial stability. Data shows that the USD/IDR exchange rate is very high, reaching its highest peak in June 2024. High inflation affects people’s purchasing power and economic stability. High inflation in the past five years was triggered by Indonesia’s dependence on imported fuel oil. In the face of inflation, monetary policies such as SBN sales can help reduce money supply and stabilize the economy. This has also led to increased poverty and unemployment, requiring the Government and Bank Indonesia to implement measures to manage inflation and stabilize the currency. Inflation is a sustained increase in the prices of basic household goods. Indonesia recorded an average annual inflation of 8.5% during the same period. Inflation not only affects purchasing power but also impacts overall economic stability.